Analgesic Usage in Elderly at Public Health Center: A study in West Java, Indonesias - Putro, Gembong Soeyono; Sastramihardja, Herri S.; Dwipa, Lazuardhi (Althea Medical Journal, 2017)
Background: Various analgesics prescriptions for elderly are not appropriate according to the guideline and can cause the increase of side effects such as gastric problems. Puskesmas as a public health center in Indonesia has an important role in anticipating this problem. The objectives of this study was to identify theÂ analgesic usage in elderly patients at the public health center. Methods: This retrospective descriptive study was conducted for 3 months at Tanjungsari public health center, Sumedang, West Java, Indonesia, using total sampling. The data was taken from 417 medical records from 2013. The data taken from medical records were: sex, analgesic drug, diagnosis, and drug for gastric problem.Results: From the collected data, the most analgesics prescribed for the elderly patients was paracetamol, followed by Piroxicam, Mefenamic acid, and Ibuprofen. Not all of the elderly patients who received NSAIDs, were given gastric drug. Conclusions: The most prescribed analgesic drug given to elderly patients at the public health center is paracetamol. [AMJ.2017;4(1):16â9]DOI:Â 10.15850/amj.v4n1.1014